Analisis Putusan Pengadilan Agama tentang Penerapan Dwangsom dan Uitvoerbaar Bij Voorraad dalam Perkara Hadhanah - Mas'ud Mas'ud; Suhar Suhar; Hermanto Harun (Center for Religious Studies and Social Empowerment Foundation, 2023)
This study aims to determine the basic considerations for the Jambi Religious Court's decision Number 946/Pdt.G/2015/PA.Jmb. in applying dwangsom to hadhanah cases. In addition, it is considered important to know the basic considerations for the Jambi Religious Court's decision Number 946/Pdt.G/2015/PA.Jmb. in applying uitvoerbaar bij voorraad to hadhanah case decisions. The method used in this research is normative (doctrinal) legal research. The approach used in this research is a case approach, while the analysis used is deductive analysis. The decision of the Panel of Judges in the hadhanah case Number: 0946/Pdt.G/2015 does not apply dwangsom so that it can be considered inappropriate and not in line with the concept of maqashid syari'ah. In certain cases the settlement of a case often takes a long time, moreover if the aggrieved party takes legal action, which is often taken to extraordinary legal remedies, namely legal remedies for judicial review, which will take years. With the granting of uitbaar bij voorraad specifically related to the lawsuit for surrendering children by relying on the objectives of Islamic law (MaqÄshid Syariâ€˜ah) in the case of one of the parents apostates and the one who is given custody of their child is a Muslim, then the child's religion will still be maintained as a follower of Islam and avoid the possibility of changing religions. Penelitian ini bertujuan untuk mengetahui dasar-dasar pertimbangan putusan Pengadilan Agama Jambi Nomor 946/Pdt.G/2015/PA.Jmb. dalam menerapkan dwangsom, uitvoerbaar bij voorraad pada putusan perkara hadhanah. Metode yang penulis pergunakan adalah metode penelitian hukum normatif (doktrinal) dengan pendekatan studi kasus. Analisis yang dipergunakan adalah analisis deduktif.Â Putusan Majelis Hakim dalam Perkara hadhanah Nomor: 0946/Pdt.G/2015 yang tidak menerapkan dwangsom dapat dinilai tidak tepat dan kurang sejalan dengan konsep MaqÄshid Syariâ€˜ah. Dalam kasus tertentu penyelesaian suatu perkara tidak jarang membutuhkan waktu yang lama, lebih-lebih bila pihak yang dirugikan menempuh upaya hukum, yang tidak jarang sampai upaya peninjauan kembali yang tentunya akan memakan waktu sampai bertahun-tahun. Dengan dikabulkan uitbaar bij voorraad khusus terkait dengan gugatan penyerahan anak dengan bersandar pada tujuan Hukum Islam (MaqÄshid Syariâ€˜ah) dalam kasus salah satu orang tuanya murtad dan yang diberikan hak asuh anaknya adalah seorang Muslim, maka agama anak akan tetap terpelihara sebagai pemeluk agama Islam dan terhindar dari kemungkinan ganti agama.